Improvement of thermostable productivity ?-amylase from local isolate Bacillus licheniformis H14. - Baghdad Science Journal (مجلة بغداد للعلوم)
(28)Bacterial local isolates of Bacillus sp. were obtained from soil samples. Isolates were tested for thermostable alpha- amylase production on solid media; fifteen isolates were able to develop clear zone around the bacterial growth after floating the plates with iodine reagent (Lugol's solution). There were further tested in submerged culture which led to selection of Bacillus sp. H14since it was the most efficient .Microbial and biochemical tests showed that the local isolate Bacillus sp.H14was refered to the species B.licheniformis that signed as H14 was refered to the species B.licheniformis H14 .,To get ahigher yield of alpha – amylase(48.70unit/mg protein) production from the local isolate B.licheniformis H14 . This study used different mutation ways such as physical way by using the physical mutagen (ultraviolet light) and chemical way by using the chemical mutagen (nitrosoguanidine). Physical mutation results showed that the local isolate B.licheniformis HM14 get higher yield of alpha – amylase production(102.10 unit/mg protein) according to killing percentage (90%) while the chemical mutation results showed that the local isolate B.licheniformis HM4 get higher yield of alpha –amylase production(100.94 unit/mg protein) from the two mutant local isolates (HM14 and HM4)were the best carbon source starch (1.5%), peptone (1.5%) as nitrogen source, calcium chloride (0.02%), sodium chloride (0.05%), magnicium phosphate (0.05%), sodium di –hydrogen phosphate (0.16%), at initial pH (5) and inoculum size 1*108 cfu/ml at (50?C) For (72) hours, using shaking incubator at (150) rpm.